A review of technologies for direct lithium extraction from low Li+ concentration aqueous solutions - Murphy, Olivia; Haji, Maha N. (Frontiers in Chemical Engineering, 2022)
Under the Paris Agreement, established by the United Nations Framework Convention on Climate Change, many countries have agreed to transition their energy sources and technologies to reduce greenhouse gas emissions to levels concordant with the 1.5 degrees Celsius warming goal. Lithium (Li) is critical to this transition due to its use in nuclear fusion as well as in rechargeable lithium-ion batteries used for energy storage for electric vehicles and renewable energy harvesting systems. As a result, the global demand for Li is expected to reach 5.11 million tons by 2050. At this consumption rate, the Li reserves on land are expected to be depleted by 2080. In addition to spodumene and lepidolite ores, Li$^+$ is present in seawater, and salt-lake brines as dissolved Li$^+$ ions. Li$^+$ recovery from aqueous solutions such as these are a potential solution to limited terrestrial reserves. The present work reviews the advantages and challenges of a variety of technologies for Li$^+$recovery from aqueous solutions, including precipitation, solvent extraction, ion sieve adsorption, ion-imprinted membrane, electrochemical, ion-exchange, electrodialysis, electrode, and electrochemical battery extraction. The techno-economic feasibility and key performance parameters of each technology, such as the Li$^+$ capacity, selectivity, separation efficiency, recovery, regeneration, cyclical stability, thermal stability, environmental durability, product quality, extraction time, and energy consumption are highlighted when available. Excluding precipitation and solvent extraction, these technologies demonstrate a high potential for Li$^+$ extraction from low Li$^+$ concentration aqueous solutions or seawater. However, further research and development will be required to transition from benchtop experiments to large-scale field and industrial applications for many of these technologies. Focus should be given to developing optimized materials for adsorbents, membranes, and electrodes for high Li$^+$ selectivity, adsorption capacity, recovery efficiency, chemical stability, thermal stability, and cyclical stability. Additionally, a comprehensive analysis of the energy consumption, energy efficiency, capital and operational expenditures, and product quality should be completed for each technology. It is anticipated that this review will bolster efforts to further improve the aforementioned technologies to meet the growing Li$^+$ demand for the global energy transition and provide a solid foundation for future research.